(untitled) - Eggerichs, Emerson; (1951-...) (U.S.A, 2004)
Based on over three decades of counseling, as well as scientific and biblical research, Dr. Emerson Eggerichs and his wife, Sarah, have taken the Love and Respect message across America and are changing the way couples talk to, think about, and treat each other. If you want to feel peace, closeness, value, and experience marriage the way God intended, this book will help you get there. (3z(BLove and Respect(3y (Bis for anyone: those in marital crisis, the happily married, engaged couples, pastors and counselors, and small groups. This dynamic and life-changing message is impacting the world, resulting in the healing and restoration of countless relationships.s
Keywords: Respect -- Religious aspects -- Christianity